Alliance or acquisition? a dyadic perspective on interfirm resource combinations - Wang, Lihua; Zajac, Edward J. (Strategic Management Journal, 2007)
Abstract For firms seeking to strategically combine their resources with those of other firms, two popular alternative governance structures emerge: alliance or acquisition. In this paper, we propose a dyadic perspective to examine how and why configurations of two firms' resources and capabilities affect the costs and benefits associated with each governance structure. More specifically, we posit that factors such as (1) the resource similarity and complementarity between a pair of firms, (2) the combined relational capabilities of a pair of firms, and (3) the partner‐specific knowledge between a pair of firms will affect the likelihood of observing that pair of firms forming an alliance vs. engaging in an acquisition. We test and find support for our hypotheses using extensive longitudinal data from a sample of the largest firms in the United States from 1991 to 2000. Copyright © 2007 John Wiley & Sons, Ltd.